Heating boilers. Heating boilers with forced draught burners. Heating boilers with forced draught burners. Special requirements for boilers with forced draught oil burners with outputs up to 70 kW and a maximum operating pressure of 3 bar. Terminology, special requirements, testing and marking Part 4, (15th August 1999) - British Standards Institution,
No abstract available